ANALYSIS OF SERVICE QUALITY, BRAND IMAGE ON RETURN VISIT INTENTION THROUGH PATIENT ATTITUDE - Fanie Nur Indriani; Endang Ruswanti; Mohamad Reza Hilmy (CV. Bunda Ratu, 2024)
Hospitals as a profit-oriented business unit need to increase the number of patient visits. Provision of quality health services and strengthening brand image can strengthen the patient's positive attitude so that there is an intention to revisit. This study aims to analyze the effect of service quality and brand image on intention to return through patient attitudes at Mekar Sari Hospital. This study involved 125 respondents who were patients at Mekar Sari Hospital, Bekasi who were collected by purposive sampling. Path analysis is performed to test the model as well as research hypotheses.Path analysis found the effect of service quality on intention to return through patient attitudes and brand image. Positive and significant influence of brand image on intention to revisit. Positive and significant influence of service quality on patient attitudes. Positive and significant influence of brand image on patient attitudes. Positive and significant influence of patient attitudes on intention to revisit. Positive and significant influence of service quality on brand image. The implications of the research results provide a good impression, a positive perspective for patients regarding MS Hospital which must improve the quality of its services for patients who visit the hospital. Implications for managers must pay attention to aspects of speed and responsiveness of service, officer attitude, brand image and promotion.